Isoprene Emission Factors for Subtropical Street Trees for Regional Air Quality Modeling. Issue 1 (1st January 2016) - Dunn‐Johnston, Kristina A.; Kreuzwieser, Jürgen; Hirabayashi, Satoshi; Plant, Lyndal; Rennenberg, Heinz; Schmidt, Susanne
Abstract : Evaluating the environmental benefits and consequences of urban trees supports their sustainable management in cities. Models such as i‐Tree Eco enable decision‐making by quantifying effects associated with particular tree species. Of specific concern are emissions of biogenic volatile organic compounds, particularly isoprene, that contribute to the formation of photochemical smog and ground level ozone. Few studies have quantified these potential disservices of urban trees, and current models predominantly use emissions data from trees that differ from those in our target region of subtropical Australia. The present study aimed (i) to quantify isoprene emission rates of three tree species that together represent 16% of the inventoried street trees in the target region; (ii) to evaluate outputs of the i‐Tree Eco model using species‐specific versus currently used, generic isoprene emission rates; and (iii) to evaluate the findings in the context of regional air quality. Isoprene emission rates of Xanthostemon chrysanthus (Myrtaceae) and Buckinghamia celsissima (Proteaceae) were 2.61 and 2.06 µg g −1 dry leaf weight h −1, respectively, whereas Harpullia pendula (Sapindaceae) was a nonisoprene emitter. We substituted the generic isoprene emission rates with these three empirical values in i‐Tree Eco, resulting in a 182 kg yr −1 (97%) reduction in isoprene emissions, totaling 6284 kg yr −1 when extrapolated to the target region. From these results we conclude that care has to be taken when using generic isoprene emission factors for urban tree models. We recommend that emissions be quantified for commonly planted trees, allowing decision‐makers to select tree species with the greatest overall benefit for the urban environment. Core Ideas: Isoprene emissions quantified for three urban Australian subtropical tree species. Modeling measured, rather than generic, emission rates reduced emissions by 97%. Xanthostemon and Buckinghamia species have low isoprene emission rates. Isoprene was not detected in Harpullia; possibly a good species for the subtropics.